Automated Home Controller Design with ASIC Implementation - Sing Yii, Bryna Ngieng; Ahmad, Nabihah; C. Uttraphan; Mat Jubadi, Warsuzarina; Ruslan, Siti Hawa; Mohd Zin, Rosnah (Multidisciplinary Applied Research and Innovation, 2021)
Safety and quality of the living environment for tenants can be incorporated by home automation technologies which could monitor and control the household applications. The current penetration of the home automation system in the market is low due to its system complexity, power consumption, lack of security system, and service interruptions upon power outages. Thus, this design aims to develop a compact and low power automated home controller that integrated comfort control, security system and automated load transfer switch feature, which advanced from the previous studies in terms of security and backup power for the home automation system. The pulse width modulation (PWM) technique is implemented in the lighting system control to enhance the energy efficiency of the home automation system. The design is developed with Verilog Hardware Descriptive Language (HDL), while a testbench for each module is written for functional verification via Synopsys VCS. To develop an integrated automated home controller with low power consumption and at the same time minimized the area, the design is optimized using 90nm TSMC process technology using Synopsys Design Compiler (DC) and Synopsys IC Compiler (IC) at logical synthesis and physical synthesis stages, respectively. In this project findings, 200Hz of duty cycle pulses is successfully simulated via PWM technique to allow the human eye not to discern light blinking during light dimming occasions in the lighting system in the top-level module. The final layout’s total power consumption and area are successfully implemented with 65.61μW and 662.44μm2, respectively. The proposed automated home system controller has successfully integrated the three features and functioned correctly by giving correct outputs while scaled down into a chip at Application Specific Integrated Circuit (ASIC) level with a small area and low total power consumption.